2016
DOI: 10.1126/science.aaf3165
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular electron transfer systems fuel cellulose oxidative degradation

Abstract: Ninety percent of lignocellulose-degrading fungi contain genes encoding lytic polysaccharide monooxygenases (LPMOs). These enzymes catalyze the initial oxidative cleavage of recalcitrant polysaccharides after activation by an electron donor. Understanding the source of electrons is fundamental to fungal physiology and will also help with the exploitation of LPMOs for biomass processing. Using genome data and biochemical methods, we characterized and compared different extracellular electron sources for LPMOs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
470
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 368 publications
(512 citation statements)
references
References 111 publications
14
470
0
9
Order By: Relevance
“…Phylogenetic prediction of the function of this flavo-oxidase is hampered by the small number of characterized members of the AA3_2 subfamily (47). Our findings are in agreement with recent findings showing that AA3_2 GMC oxidoreductases can serve as extracellular electron sources for LPMOs (38,39), thus extending the array of fungal redox partners in filamentous fungi. Overall, the present data suggest that compensatory mechanisms indeed enable P. anserina to cope with lack of CDH for the most part.…”
Section: Resultssupporting
confidence: 81%
“…Phylogenetic prediction of the function of this flavo-oxidase is hampered by the small number of characterized members of the AA3_2 subfamily (47). Our findings are in agreement with recent findings showing that AA3_2 GMC oxidoreductases can serve as extracellular electron sources for LPMOs (38,39), thus extending the array of fungal redox partners in filamentous fungi. Overall, the present data suggest that compensatory mechanisms indeed enable P. anserina to cope with lack of CDH for the most part.…”
Section: Resultssupporting
confidence: 81%
“…These oxidative biocatalysts are activated in the presence of an electron donor molecule to facilitate cellulose degradation (2,3). Extensive studies have been performed to identify its potential redox partner, which led to the prediction of diverse exogenous (lignin, ascorbate or photosynthetic pigment) (4), and endogenous (dehydrogenases or oxidoreductases) (18,33) reductants.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have also shown that a combination of AA9 protein and a co-secretory CDH (cellobiose dehydrogenase) could cleave pure cellulose (17). The identification of CDHs as redox partner for LPMO (18) was primarily dependant on (i) available secretome data which has given evidence about CDH as a LPMO co-secretory proteins and (ii) on theoretical understanding of the electron transport processes involved in LPMO activation (17,(19)(20)(21)(22). However, there are many filamentous fungi which do not secrete CDH (because of obvious lack of encoding gene) and in contrast many ascomycetes are known to encode multiple CDHs (20), suggesting that the choice of redox partner is very specific to type of LPMO and no general concept exist.…”
Section: Introductionmentioning
confidence: 99%
“…W hen microbial cells cannot import or are physically separated from metabolic electron donors or acceptors, diffusible compounds can act as electron carriers and support survival on these substrates (1,2). These conditions arise in the presence of poised-potential electrodes or insoluble minerals, such as iron oxides (3)(4)(5), and in multicellular communities (biofilms) where the formation of chemical gradients leads to oxidant limitation for cells at depth (6)(7)(8)(9).…”
mentioning
confidence: 99%